The hazards of using probability and statistics like tools for legal assessment - Ana Sánchez-Rubio (Revista Brasileira de Direito Processual Penal)
In the common use of the expression, to prove means to test, to check, as a way of demonstrating. These days, the criminal proceedings, in order to achieve the nearest demonstration to the certainty or, in legal language, to the material truth, uses some tools of mathematical field for giving more strength to evidentiary result. In this regard, the probability product of statistics is increasingly occupying a major role. This paper aims to reveal the hazards that involve trusting completely of numerical data in legal assessment, particularly if the parties of the proceedings misinterpret mathematical results, since that could seriously influence on the judicial decision foundation.